2006
DOI: 10.1002/da.20140
|View full text |Cite
|
Sign up to set email alerts
|

Is selective mutism associated with deficits in memory span and visual memory?: an exploratory case–control study

Abstract: Our main aim in this study was to explore the association between selective mutism (SM) and aspects of nonverbal cognition such as visual memory span and visual memory. Auditory-verbal memory span was also examined. The etiology of SM is unclear, and it probably represents a heterogeneous condition. SM is associated with language impairment, but nonspecific neurodevelopmental factors, including motor problems, are also reported in SM without language impairment. Furthermore, SM is described in Asperger's syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
1
13
0
6
Order By: Relevance
“…Notwithstanding the group by sex interaction, there was a significant main effect for group on receptive vocabulary ability with children with SM scoring significantly lower (but within the age-appropriate range) than community controls. This is consistent with previous studies that have found lower scores on the PPVT-III in children with SM (Kristensen & Oerbeck, 2006;Manassis et al, 2007;McInnes et al, 2004). Unlike these previous studies, however, we did not find any significant differences between the SM and the mixed anxiety groups in receptive vocabulary scores.…”
Section: Language Skillssupporting
confidence: 91%
See 1 more Smart Citation
“…Notwithstanding the group by sex interaction, there was a significant main effect for group on receptive vocabulary ability with children with SM scoring significantly lower (but within the age-appropriate range) than community controls. This is consistent with previous studies that have found lower scores on the PPVT-III in children with SM (Kristensen & Oerbeck, 2006;Manassis et al, 2007;McInnes et al, 2004). Unlike these previous studies, however, we did not find any significant differences between the SM and the mixed anxiety groups in receptive vocabulary scores.…”
Section: Language Skillssupporting
confidence: 91%
“…For example, some researchers have reported that children with SM perform significantly lower than community controls on academic measures (Bergman et al, 2002;Kristensen & Oerbeck, 2006;Schwartz, Freedy, & Sheridan, 2006), especially language abilities (Manassis et al, 2007;McInnes et al, 2004). In comparison, other studies have found no differences between children with SM and community controls (Cunningham et al, 2004).…”
mentioning
confidence: 99%
“…Given that SM most often presents itself in the school setting and with unfamiliar individuals, such as teachers, many studies have focused on the functioning of children with SM in tasks associated with the school setting, such as language and academic development [2,4,[15][16][17][18][19]. However, almost no research has investigated the quality of interactions between children with SM and their parents.…”
Section: Introductionmentioning
confidence: 98%
“…Par ailleurs, aucune différence n'est retrouvée entre enfants présentant une dyslexie et enfants contrôles (Symmes & Rapoport, 1972 ;Vellutino, Smith, Steger & Kaman, 1975). Dans une étude comparant des enfants présentant un mutisme sélectif à un groupe contrôle, Kristensen et Oerbeck (2006) trouvent que la note concernant les fonctions motrices est la plus prédictive des résultats au BVRT (administration A et formes C), devant celles des fonctions langagières et des fonctions intellectuelles.…”
Section: Utilisationunclassified